Kajian penilaian prestasi komiti sekolah dalam pengurusan fasiliti di sekolah dasar di Kabupaten Batubara, Indonesia - Hasbullah, Amilia (2012)
School Committee is known as a key player in the practice of school based management principles which allow the community to play an important role in order to determine the quality of education. It involves school facility management as a mean to ensure an effective teaching and learning environment. However, the lack of School Committee involvement has become an issue and influenced on the quality of education particularly on school facilities. Therefore, the objective of this research is to address the performance of School Committee within the management of school facilities. Accordingly, primary school of Batubara District was chosen as a case study. In this research, the concept of facility management process and Logometrix Model were introduced as a basis to develop a framework on measuring the level of School Committee performance within school facility management. The standard of Indonesian school facility was used as the criteria on the measurement of School Committee performance. Mixed method was deployed to execute this research. The qualitative aspect involved semi structured interviews with the School Committee members of seven public primary schools in Batubara District. The interview addressed that School Committee required school facility management criteria as an effort to improve the level of School Committee involvement. Subsequently, quantitative approach deployed through 381 questionnaires distributed to stakeholders who work with and use school facilities in public primary school which spread over seven sub districts. The result revealed that the level of School Committee involvement in school facility management is low. The result on both quantitative and qualitative concluded that performance within school facility management needs to be improved.